(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the structural, semantic, and functional features of neologisms in George Orwell’s 1984 and Margaret Atwood’s The Handmaid’s Tale from a comparative lexicological perspective. Although many scholars have explored the political and ideological dimensions of these dystopian novels, the role of neologisms as mechanisms of vocabulary expansion and lexical innovation has received less focused attention. This study aims to analyze how both authors use neologisms to construct dystopian realities, shape ideological discourse, and expand lexical systems within literary language. Through literary analysis, comparative analysis, semantic interpretation, and discourse analysis, the research identifies major patterns of word formation, semantic transformation, and stylistic function in both works. The results demonstrate that Orwell primarily employs compounding, abbreviation, and lexical reduction to represent political domination, while Atwood relies more heavily on semantic shifts, religiously redefined vocabulary, and socially constructed terminology to depict patriarchal oppression. Despite their differences, both authors use neologisms as powerful tools of social control and world-building. This research contributes to literary lexicology by showing that dystopian fiction serves as an important source of vocabulary expansion and conceptual innovation in modern English.